(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. Il Diritto come legittimazione - 3. La corrispondenza tra istituzione e ordinamento - 4. La terzietà del Diritto - 5. La non-necessarietà del legislatore affinché si abbia vero Diritto - 6. Per concludere. Legal Order and Canon law: The Structuring Contribution of Santi Romano ABSTRACT: The contribution of the State’s System Theory of Santi Romano is decisive for illustrating and protecting the singularities of Canon Law without jeopardizing its intrinsic juridical nature, rather, by confirming it precisely because of the “institutional” nature of the Church. The substantial contributions that "L’ordinamento giuridico" offers to the systematic and dogmatic understanding of Canon Law are four: law as legitimacy, the conformity between institution and legal system, the neutrality of the law, the non-necessity of the Legislator in order to have true law.